Computational Paradigm to Elucidate the Effects of Arts-Based Approaches: Art and Music Studies and Implications for Research and Therapy - Sandak, Billie; Gilboa, Avi; Harel, David (Frontiers in Psychology, 2020)
Art therapy and music therapy, as well as other arts-based approaches and interventions help mitigate symptoms in serious and chronic diseases, and to improve the wellbeing and quality of life for both, healthy individuals and patients. Artistic creation is also researched and practiced intending to empower and understand individuals, groups and communities. However, much research is required in order to learn how arts-based approaches operate and to enhance their effectivity. The complex and simultaneous occurrences involving the dynamics of the creation work, the client and the therapist in a typical arts setting are difficult to grasp, and consequently, affecting their objective analyses. Here we employ our Computational Paradigm which enables the quantitative and rigorous tracking, analyzing and documenting of the underlying dynamic processes, and describe its application in recent past and current real-world art and music studies with human participants. We aim to study emergent artistic behaviors of individuals and collectives in response to art and music making. Significant insights obtained include demographic variation factors such as gender and age, empirical behavioral patterns, and quantitative expressiveness and its change. We discuss the implications of the findings for therapy and research, such as causality for behavioral diversification and audio-visual cross-modality, and also offer directions for future applications and technology enhancements.